Pengembangan Model Sistem Informasi Manajemen Dokumen Mutu STKIP PGRI Lubuklinggau - Armi Yuneti; Marianita Marianita; Ahmad Gawdy Prananosa; Donni Pestalozi; M.Rusni Eka Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aims to manage quality document data based on information technology. The stages of this research method include; 1) requirements analysis, 2) design, 3) implementation and unit testing. 4) integration and system test. The approach in this study uses a systems approach with the waterfall model. The steps for developing a software model with a waterfall model are divided into 4 cycles, namely; 1) requirements analysis, 2) design, 3) implementation and unit testing. 4) integration and system test. The results of the study, 1) menu components and SOP submenus are feasible for use, 2) Standard Quality menu and submenu components are feasible for use, 3) quality manual menu and submenu components are feasible for use, 4) menu components and formuruclear submenus are suitable for use. In conclusion, the Quality Document SIM is feasible to use. The Quality Document Database Management Information System can assist LP3MP in managing data online, so that the LP3MP operator team can (input, process and output data) quickly, precisely and accurately. Keywords: SIM, Database, Quality Documents